Modifikasi Bioplastik Berbasis Pati-Polivinil Alkohol (PVA) Dengan Cross-Linking Agent Asam Sitrat Dan Pemplastis Gliserol - Herlili Peronika; Bahruddin Bahruddin; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bioplastic characteristics are influenced by various parameters, including levels of cross linking agents (such as citric acid) and plasticizers (such as glycerol). The research was to study the effect of citric acid and glycerol levels on mechanical properties, cross linking (characterized by ester groups), and biodegradation of bioplastics based starch-polyvinyl alcohol (PVA). Bioplastic manufacturing is done by mixing sago starch -PVA (1: 3), glycerol (10, 15, 20% w/w) and citric acid (2.5; 5; 7.5% w/w) at 90ºC for 45°C minutes, optimization of process conditions is determined by response surface methodology (RSM). The parameters tested include tensile strength test, elongation, and biodegradation. The most significant factor affecting all responses was the level of citric acid and glycerol. The optimum process conditions were obtained at 7.5% w / citric acid content and glycerol 19.63% w / w with a tensile strength response of 21 MPa, elongation 566.6%, and 55.63% biodegradation. Keywords: bioplastics, citrid acid, glycerol, polyvinyl alcohol, RSM, sago starch